SEKOLAH RAMAH ANAK TERHADAP PENGEMBANGAN SOSIO-EMOSIONAL ANAK DI SD NEGERI NGUPASAN YOGYAKARTA - Muhammad Majdi; Ahmad Shofiyuddin Ichsan (Pepatudzu : Media Pendidikan dan Sosial Kemasyarakatan, 2021)
School being a source of stress among students seems to be a reality that all circles need to anticipate. As a formal educational institution, school has to have a friendly nature, both friendly to children and friendly to the environment, so that they can have a positive effect on children's socio-emotional development. The purpose of this research is to reveal how the contribution of Child Friendly School (SRA) in the socio-emotional development of children at SD Negeri Ngupasan Yogyakarta. This research is qualitative and the research method used is descriptive-inductive method. Data are collected and described through in-depth observations and interviews, while the data analysis method applied is Cresswell's qualitative data. The results show that the Child Friendly School (SRA) has a contribution in the socio-emotional development of children at SD Negeri Ngupasan Yogyakarta. The stages of the Child Friendly School Program include: 1) Anti-violence policies; 2). Implementation of the curriculum; 3 Educators and education personnel trained in child rights; 4). Facilities and infrastructure; 5). Student participation; and 6) Parental participation. The contribution obtained from the implementation of the Child Friendly School program in socio-emotional development is that students could respect others, more able to control emotions, responsive, bound by parental figures, care, imitate their friends, play games that use rules and create them, following an event, confident, tolerant, cooperative and responsible, and tend to spend time with friends.